THE USE OF THE FLY SWATTER GAME TO TEACH VOCABULARY MASTERY TO THE SEVENTH-GRADE STUDENTS - Marliasari, Sherly; Adawiyah, Dita; Yolanda, Shely; Dirgantara, Erwan; Sulaiman, Mgs (English Community Journal, 2023)
Vocabulary is one of language elements that are needed in learning and communication. The aimed of the study was to find out whether teaching vocabulary mastery using fly swatter game in vocabulary mastery significant or not. The method used quasi experimental method. The population of this research was all the seventh grade’ students of SMP Negeri 6 Palembang with total was 372 students. The samples took out were 68 students from 372 students by using purposive sampling method. They divided into the experimental and control group. The data were collected by using written test, those were pretest and posttest. The result of the test was analyzed by independent sample t-test. The mean in posttest of experimental group was 72.71, it was higher than the mean posttest of the control group which was 58.65. The result of T-Test obtained significance (sig. 2 tailed) was 0.002, which less or lower than 0.05. Since the sig. 2 tailed was less than 0.05, so the null hypothesis Ho was rejected and the alternative hypothesis Ha was accepted. It means that there was significant difference on students’ vocabulary mastery taught using Fly Swatter game than those who are not.